COVID-19 Crisis Through a Migration Lens - World Bank (World Bank, Washington, DC, 2020)
The economic crisis induced by COVID‐19 could be long, deep, and pervasive when viewed through amigration lens. Lockdowns, travel bans, and social distancing have brought global economic activities to a near standstill. Host countries face additional challenges in many sectors, such as health and agriculture, that depend on the availability of migrant workers. Migrants face the risk of contagion and also the possible loss of employment, wages, and health insurance coverage. This Migration and Development Brief provides a prognosis of how these events might affect global trends in international economic migration and remittances in 2020 and 2021. Considering that migrants tend to be concentrated in urban economic centers (cities), and are vulnerable to infection by the coronavirus, there is a need to include migrants in efforts to fight thecoronavirus. Migrant remittances provide an economic lifeline to poor households in many countries; a reduction in remittance flows could increase poverty and reduce households’ access to much‐needed health services. The crisis could exacerbate xenophobic, discriminatory treatment of migrants, which calls for greater vigilance against such practices. This Brief is largely focused on international migrants, but governments should not ignore the plight of internal migrants. The magnitude of internal migration is about two‐and‐a‐half times that of international migration. Lockdowns, loss of employment, and social distancing prompted a chaotic and painful process of mass return for internal migrants in India and many countries in Latin America. Thus, the COVID‐19 containment measures might have contributed to spreading the epidemic. Governments need to address the challenges facing internal migrants by including them in health services and cashtransfer and other social programs, and protecting them from discrimination.